Bond-graph based substructuring of dynamical systems. - Gawthrop, P.J (Earthquake engineering & structural dynamics.)
A bond graph approach to hybrid simulation of dynamical systems using numerical-experimental real-time substructuring is presented. The bond graph concepts of a virtual junction and a virtual actuator, hitherto used in the context of physical model based control, are used to perform the substructuring in an intuitively appealing way. The approach is illustrated by the reworking of a previously published example. The approach is verified experimentally using a bench top multiple mass spring system for the physical substructure and automatically generated real time code is used to implement the numerical substructure.